2000
DOI: 10.1126/science.290.5499.2155
|View full text |Cite
|
Sign up to set email alerts
|

Functional Requirement for Class I MHC in CNS Development and Plasticity

Abstract: Class I major histocompatibility complex (class I MHC) molecules, known to be important for immune responses to antigen, are expressed also by neurons that undergo activity-dependent, longterm structural and synaptic modifications. Here, we show that in mice genetically deficient for cell surface class I MHC or for a class I MHC receptor component, CD3ζ, refinement of connections between retina and central targets during development is incomplete. In the hippocampus of adult mutants, N-methyl-D-aspartate recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

37
849
4
20

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 755 publications
(940 citation statements)
references
References 40 publications
37
849
4
20
Order By: Relevance
“…However, very little is known about the cell type-specific expression of neolacto-series gangliosides in murine organs. Increased expression of ganglioside IV 6 nLc4(C 24 ) in the brain of b 2 M-/-compared with the control b 2 M+/-mice may be related to the role of class I MHC molecules in the central nervous system [3]. It has been shown that class I MHC molecules are expressed by specific sets of neurones that undergo activity-dependent changes [46], and that mice lacking either b 2 M or CD3z exhibit abnormalities in connections between these neurones [3].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, very little is known about the cell type-specific expression of neolacto-series gangliosides in murine organs. Increased expression of ganglioside IV 6 nLc4(C 24 ) in the brain of b 2 M-/-compared with the control b 2 M+/-mice may be related to the role of class I MHC molecules in the central nervous system [3]. It has been shown that class I MHC molecules are expressed by specific sets of neurones that undergo activity-dependent changes [46], and that mice lacking either b 2 M or CD3z exhibit abnormalities in connections between these neurones [3].…”
Section: Discussionmentioning
confidence: 99%
“…Increased expression of ganglioside IV 6 nLc4(C 24 ) in the brain of b 2 M-/-compared with the control b 2 M+/-mice may be related to the role of class I MHC molecules in the central nervous system [3]. It has been shown that class I MHC molecules are expressed by specific sets of neurones that undergo activity-dependent changes [46], and that mice lacking either b 2 M or CD3z exhibit abnormalities in connections between these neurones [3]. Neolacto-series gangliosides are well characterized in acoustic neurinoma samples [47] and the peripheral nervous system [48] *Density of individual bands was expressed as the percentage of the total density for all bands.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bouzat et al (2011) Besides its important effects on the SHH pathway, CEPO might exert its beneficial effects on nerve cells through its action on MHC-I (major histocompatibility complex type I) molecules. MHC-I molecules are involved in nerve plasticity and play an important role in nerve cell recovery by increasing outgrowth of axons in injured neurons (Oliveira et al, 2004;Fu et al, 2010;Huh et al, 2000). In this context, the immunomodulatory effects of CEPO induce stable improvement in neurite outgrowth, which is crucial in restoring the CNS after injury (Fu et al, 2010;Adembri et al, 2008;Schmidt et al, 2008).…”
Section: Mechanisms For Neuroprotection/neurorescuementioning
confidence: 99%
“…The MHC-I (major histocompatibility complex class I) proteins, a key player in adaptive immunity, is enriched in synaptic fractions and the deficiency of which can result in enlarged neural projections [65]. MHC-I can negatively regulate synapse density during the formation of cortical connections via signaling pathways which require MEF2, an ASD candidate gene [66,67].…”
Section: Immune Dysregulation In Asdmentioning
confidence: 99%